PURCHASE INTENTION OF FASHION PRODUCT AS AN IMPACT OF DIGITAL MARKETING, MEDIATED BY CUSTOMER ENGAGEMENT IN THE GENERATION Z - Thomas Stefanus Kaihatu (Institute of Research and Community Outreach - Petra Christian University, 2020)
This research is to study the impact of digital marketing on consumer engagement and purchase intention, consumer engagement on purchase intention, and the mediating effect of consumer engagement in the relation between digital marketing and purchase intention. The population in this research was generation Z. Samples were 236 students in two private universities in Surabaya. Data were analyzed with Andrew Hayes PROCESS model 4. The results show that all hypotheses were supported. The findings of this research contribute to the online communication strategy of online shop owners to reach generation Z